Type specimen sequencing, multilocus analyses, and species delimitation methods recognize the cosmopolitan Corallina berteroi and establish the northern Japanese C. yendoi sp. nov. (Corallinaceae, Rhodophyta) - Calderon, Martha S.; Bustamante, Danilo E.; Gabrielson, Paul W.; Martone, Patrick T.; Hind, Katharine R.; Schipper, Soren R.; Mansilla Muñoz, Andres Omar (My University, 2021)
A partial rbcL sequence of the lectotype specimen of Corallina berteroi shows that it is the earliest available name for C. ferreyrae. Multilocus species delimitation analyses (ABGD, SPN, GMYC, bPTP, and BPP) using independent or concatenated COI, psbA, and rbcL sequences recognized one, two, or three species in this complex, but only with weak support for each species hypothesis. Conservatively, we recognize a single worldwide species in this complex of what appears to be multiple, evolving populations. Included in this species, besides C. ferreyrae, are C. caespitosa, the morphologically distinct C. melobesioides, and, based on a partial rbcL sequence of the holotype specimen, C. pinnatifolia. Corallina berteroi, not C. officinalis, is the cosmopolitan temperate species found thus far in the NE Atlantic, Mediterranean Sea, warm temperate NW Atlantic and NE Pacific, cold temperate SW Atlantic (Falkland Islands), cold and warm temperate SE Pacific, NW Pacific and southern Australia. Also proposed is C. yendoi sp. nov. from Hokkaido, Japan, which was recognized as distinct by 10 of the 13 species discrimination analyses, including the multilocus BPP.
Keywords: coralline algae; corallina caespitosa; c; ferreyrae; c; melobesioides; c; pinnatifolia; multilocus phylogeny; new species; species boundaries